2008
DOI: 10.1123/rsj.32.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Selected Risk Management Policies, Practices, and Procedures for Intramural Activities at NIRSA Institutions

Abstract: A survey of all National Intramural-Recreational Sports Association (NIRSA) campus recreation directors was conducted to determine the risk management policies, practices, and procedures relating to intramural activities and recreational sports at colleges and universities throughout North America. The survey instrument, in its final form, addressed practices, policies, and procedures of campus recreation directors through 44 questions relating to the following areas: (a) documentation, (b) medical factors, (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Since the 1990s, recreational sport professionals have realized importance of effective risk management practices, and risk management practices among recreational sport professionals have been improved (Mulrooney& Styles, 2005). Risk management studies agree that the use of risk management plans and manuals has been an excellent managerial practice to provide quality services and to continue financial wellbeing (Lee, Farley, & kwon, 2010;Mulrooney & Green, 1997;Stier, Schneider, Kampf, Haines, & Gaskins, 2008;Young, et al, 2007). Yong et al (2007) claimed that recreational sport directors were aware of and concerned about the risk issues most oftenlitigated and took the proper steps to reduce the incidence of risk issues becoming litigations and to successfully defend the litigations that were filed.…”
Section: Risk Management Plansmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1990s, recreational sport professionals have realized importance of effective risk management practices, and risk management practices among recreational sport professionals have been improved (Mulrooney& Styles, 2005). Risk management studies agree that the use of risk management plans and manuals has been an excellent managerial practice to provide quality services and to continue financial wellbeing (Lee, Farley, & kwon, 2010;Mulrooney & Green, 1997;Stier, Schneider, Kampf, Haines, & Gaskins, 2008;Young, et al, 2007). Yong et al (2007) claimed that recreational sport directors were aware of and concerned about the risk issues most oftenlitigated and took the proper steps to reduce the incidence of risk issues becoming litigations and to successfully defend the litigations that were filed.…”
Section: Risk Management Plansmentioning
confidence: 99%
“…As a number of publications indicated (Lee et al, 2010;Stier, et al, 2008;Young, 2001Young, , 2007, essential legal topics within the scope of work for golf directors may include tort law, contract law, premises liability, participatory and contractual forms, negligence, human resources laws, product liability, fiduciary responsibilities, constitutional law, and administrative law. Since a comprehensive risk management manual not only helps to reduce the frequency of legal claims, but also generates an environment where the inherent risks are minimized (Cooper, 1997;Lee et al, 2010), golf directors should create asound risk management plan that serves the customer, the employee, and the organization.…”
Section: Risk Management Plansmentioning
confidence: 99%
“…Since its development, numerous variations of the sportsmanship rating system have sprouted in collegiate intramural programs throughout the United States, and are being used to monitor and enforce sportsmanship (Vincent and Kearney, 2001). The most prevalent conceptual system used is the Sportsmanship Rating System (SRS), and Stier, Schneider, Kampf, Haines, and Gaskins (2008) reported that over two-thirds of National Intramural-Recreational Sports Association (NIRSA) institutional member schools have implemented some form of an SRS.…”
Section: Sportsmanship Rating Systemmentioning
confidence: 99%
“…
This qualitative case study explored the manner by which team captains and intramural players were educated about the Sportsmanship Rating System (SRS) used by their intramural sports program and their perceptions about the SRS. While some form of an SRS is widely used by NIRSA members (Stier et al, 2008), virtually no research has been conducted as to its effectiveness. The site was a medium sized, public, four year institution in the mid-Atlantic region.
…”
mentioning
confidence: 99%
“…In an effort to provide a safe environment, high school athletic directors must constantly ensure that the facilities, equipment, and supplies, as well as the processes associated with sport activities are safe for the participants and fans (Stier et al, 2008). To achieve such a goal, extensive planning is essential (Stier et al, 2008). Due to the nature of outdoor athletic activities, coaches and schools must be constantly prepared to respond to threatening weather.…”
Section: Introductionmentioning
confidence: 99%